Efisiensi Produksi Usaha Sapi Perah Rakyat (Studi Kasus pada Peternak Anggota Koperasi Usaha Peternakan dan Pemerahan Sapi Perah Kaliurang, Sleman, Yogyakarta) (Production Efficiency of Smallholder Dairy Cattle Farming (Case Study on The Farmer Members of - Melani Astuti; Rini Widiati; Yustina Yuni Suranindyah (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The objective of the study was to investigate rationality and allocative efficiency of the utilisation of production factors in smallholder dairy farmers. The study was conducted from June to August 2009 in the region of UPP Kaliurang cooperative, Sleman, Yogyakarta. There were forty respondents of smallholder dairy farmers taken by purposive sampling method. The primary data were taken from respondents and secondary data were from related institutions. Regression function of Cobb-Douglass model was used to determine the production factor which influenced milk production. Data were analysed based on unit/farmer. Coefficient of regression was estimated with Ordinary Least Square (OLS), further analysis was conducted by allocative efficiency. The result of this study showed that forage, concentrate, land owned/farmer, labor, number of livestock and percentage of lactating cows significantly affected the milk production (R2=0.78). Partially, percentage of lactating cows and total dairy cows had positive effect (P<0.01 and P<0.1) on the milk production of each farmer, however forage and concentrates did not affect the milk production. The result of allocative efficiency test showed that input consisted of forage and concentrates in this study have not achieved efficienly. Technically, the utilisation of production factors had not been rational, it was shown by the production elasticity (Ep) >1 (1.462).(Key words: Production of efficiency, Smallholder dairy farming, Factors of production)